Pengaruh Kondisi Internal, Kondisi Debitur dan Kondisi Lingkungan Terhadap Non Performing Loans (NPL) dengan Variabel Mediasi Jumlah Kredit (Studi Pada Bank Mandiri Cabang Sungai Bahar) - Mukti Dian S; Afrizal; Enggar Diah PA (Jurnal Akuntansi & Keuangan Unja, 2020)
This research aims to determine and analyze the influence of internal conditions, debtor conditions, and environmental conditions on the number of loans with NPL as a mediating variable at PT. Bank Mandiri Cabang Sungai Bahar. The population of this research included all customers with the sampling technique used was the Slovin formula so that the sample taken was 117 customers. The analysis technique used is to use multiple regression and path analysis. The result of this research showed that partially, internal conditions significantly affected the number of loans, debtor conditions and environmental conditions did not significantly affect the number of loans and had a significant positive effect on non-performing loans (NPL). Internal conditions, debtor conditions and environmental conditions significantly influence non-performing loans (NPL). Internal conditions, debtor conditions and environmental conditions and the amount of credit simultaneously influence the non-performing loans (NPL). The amount of credit has an effect as an intervening variable internal conditions to NPL. The amount of credit has no effect as an intervening variable on the condition of the debtor and environmental conditions on non-performing loans (NPL).